The Community of Rights: Human Rights and the Concept of Nature in the Context of the French Revolution and the Terror - Kjærsgård, Jonas Ross (Academic Quarter | Akademisk kvarter, 2012)
This article is about the negotiation of the limits of the community of rights in the age of the French Revolution and the Reign of Terror, and it has a special emphasis on the question of women’s rights. The relatively unknown author and political activist Olympe de Gouges is used as a case with focus on the radical and egalitarian part of her thinking. De Gouges’s challenge to a normative understanding of sexual differences and her defense of women’s and illegitimate children’s rights are examples of how the rhetoric of human rights and the idea of the natural has been operationalized in a way that made it possible to see and criticize the fact that women were excluded from the political sphere as long as equality among brothers was the sole alternative to the paternal authority of the king.